ANALISIS INTERAKSI SIMBOLIK KAUM LESBIAN BUTCH DENGAN MASYARAKAT LINGKUNGANNYA - Masyitah, Masyitah (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2016)
For some people in Indonesia to discuss the word - the word lesbian istaboo, where it becomes something that is prohibited by religion and culture in Indonesia. Its existence is recognized as a reality within the society and cause a variety of reactions by the surrounding environment. To obtain recognition of the existence of identity aslesbian from surrounding communities, lesbians should be involved in the process of social interaction. When lesbians express themselves and interact through interpersonal communication there must be pressure - felt a certain pressure to decide what will be disclosed and what should be kept secret. Furthermore, the impression management theory and identity theory stating whether they are acceptable or not with the impression that theymake and their true identities. Theory of communication privacy settings / Communication Privacy Management (CPM) said there were risks and rewards generated by the decisions made for the people with whom lesbians interact. The study looked at how lesbians about themselves and then observe how lesbians interact with people around them that are formed in their social interaction through the case study method. Based on this research, some lesbians can express themselves in the community through symbolic interaction. The results showed some lesbians may declare himself to the community through symbolic interaction. Lesbians who have an understanding of positive self-concept is easier to open up or do a good communication with the public. With the boundaries of private information and within the boundaries of their collective acceptable and appreciated. In general, in the lesbian community or same-sex interaction only they can interact well, of course, with a gesture, a look, a signal- specific signals that can only be understood by his people along with its own language. The conclusion of this study noted that the symbolic interaction lesbians want to show to the surrounding environment, that lesbiansare interesting person and want to get acceptance or acknowledgment by a symbol - a symbol that they have. Suggestions on this research to the public is able to see that the potential of lesbians and lesbian people should look is part of the environment and respecting the environment and not ostracized.